Non-HLA Gene Polymorphisms in the Pathogenesis of Type 1 Diabetes: Phase and Endotype Specific Effects - Laine, Antti-Pekka; Valta, Milla; Toppari, Jorma; Knip, Mikael; Veijola, Riitta; Ilonen, Jorma; Lempainen, Johanna (Frontiers in Immunology, 2022)
The non-HLA loci conferring susceptibility to type 1 diabetes determine approximately half of the genetic disease risk and several of them have been shown to affect immune-cell or pancreatic β-cell functions. A number of these loci have shown association with the appearance of autoantibodies or with progression from seroconversion to clinical type 1 diabetes. In the current study, we have re-analysed 21 of our loci with prior association evidence using an expanded DIPP follow-up cohort of 976 autoantibody positive cases and 1910 matched controls. Survival analysis using Cox regression was applied for time periods from birth to seroconversion and from seroconversion to type 1 diabetes. The appearance of autoantibodies was also analysed in endotypes, which are defined through the first appearing autoantibody, either IAA or GADA. Analysing the time period from birth to seroconversion, we were able to replicate our previous association findings at PTPN22, INS, and NRP1. Novel findings included associations with ERBB3, UBASH3A, PTPN2 and FUT2. In the time period from seroconversion to clinical type 1 diabetes, prior associations with PTPN2, CD226 and PTPN22 were replicated and a novel association with STAT4 observed. Analysing the appearance of autoantibodies in endotypes, the PTPN22 association was specific for IAA-first. In the progression phase STAT4 was specific for IAA-first and ERBB3 to GADA-first. In conclusion, our results further the knowledge of the function of non-HLA risk polymorphisms in detailing endotype specificity and timing of the disease development.